2015
DOI: 10.1007/s11084-015-9460-3
|View full text |Cite
|
Sign up to set email alerts
|

Timescales of Oxygenation Following the Evolution of Oxygenic Photosynthesis

Abstract: Among the most important bioenergetic innovations in the history of life was the invention of oxygenic photosynthesis-autotrophic growth by splitting water with sunlight-by Cyanobacteria. It is widely accepted that the invention of oxygenic photosynthesis ultimately resulted in the rise of oxygen by ca. 2.35 Gya, but it is debated whether this occurred more or less immediately as a proximal result of the evolution of oxygenic Cyanobacteria or whether they originated several hundred million to more than one bil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(71 citation statements)
references
References 115 publications
8
62
1
Order By: Relevance
“…For example, Ward et al. () calculated that the planet could have become oxygenated within just one hundred thousand years from the origin of oxygenic photosynthesis. Thus, in a hypothetical scenario in which a non‐photosynthetic ancestor of Cyanobacteria obtained photosynthesis via HGT from an anoxygenic phototroph, and this transferred reaction center evolved standard levels of oxygen evolution within one hundred thousand years (ΔT = 0.1 Ma), then ν max would need to be more than 400 thousand amino acid changes per site per Ga, which is orders of magnitude greater than the rate of evolution of any known protein (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Ward et al. () calculated that the planet could have become oxygenated within just one hundred thousand years from the origin of oxygenic photosynthesis. Thus, in a hypothetical scenario in which a non‐photosynthetic ancestor of Cyanobacteria obtained photosynthesis via HGT from an anoxygenic phototroph, and this transferred reaction center evolved standard levels of oxygen evolution within one hundred thousand years (ΔT = 0.1 Ma), then ν max would need to be more than 400 thousand amino acid changes per site per Ga, which is orders of magnitude greater than the rate of evolution of any known protein (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…We denote this span of time by ΔT. If ΔT is small, such as a few million years or less for example, then the evolution of oxygenic photosynthesis may be better described as a sudden and fast process only getting started shortly before the GOE as suggested by some recent analyses (Shih, Hemp et al., ; Ward, Kirschvink, & Fischer, ). On the other hand, if ΔT is large: Several hundred million years or more for example, then the earliest stages in the evolution of oxygenic photosynthesis could significantly predate the GOE as suggested by some geochemical (Mukhopadhyay et al., ; Planavsky et al., ; Satkoski, Beukes, Li, Beard, & Johnson, ) and phylogenetic data (Blank & Sanchez‐Baracaldo, ; Schirrmeister, de Vos, Antonelli, & Bagheri, ).…”
Section: Introductionmentioning
confidence: 99%
“…While substantial debate exists about the antiquity of Cyanobacteria, multiple lines of evidence suggest that oxygenic photosynthesis evolved only shortly before the GOE Johnson et al, 2013a;Shih et al, 2017;Ward, Kirschvink, & Fischer, 2016), and therefore, molecular oxygen derived from photosynthesis was unlikely to play a role in Archean BIF formation. 2.3 Ga.…”
Section: Discussionmentioning
confidence: 99%
“…Ward et al . ( 180 ) modeled the GOE as the initial appearance of oxygenic photosynthesis but similarly concluded that the oxic transition was rapid. Our simple model of bacterial sequence evolution, introduced above, would suggest that shifting redox conditions would quickly be exploited by bacteria with novel physiologies that make use of oxygen in energy metabolism or biosynthesis.…”
Section: A Theoretical Framework For the Evolutionary Timetablementioning
confidence: 99%